Suplementasi Fucoidan Padina dari Perairan Lampung untuk Meningkatkan Respon Imun Udang Vannamei - Setyawan, Agus; Lestari, Kiki Indah; Adiputra, Yudha Trinoegraha (Journal of Tropical Marine Science, 2024)
Padina, one of the brown algae, grows in many tropical waters including in Lampung. Padina contains fucoidan, a sulfated polysaccharide, which has been shown to have a wide range of bioactivity. This study aims to determine the effectiveness of fucoidan Padina sp. from Lampung waters to enhance the non-specific immune response in Pacific white shrimp. Padina sp. was collected from Ketapang Beach, Pesawaran, Lampung then the Padina’s fucoidan was acidly extracted by previously method. Fucoidan then supplemented to 10 vananmei shrimp (size 10 g) each container (45 L) for 14 days. The study was conducted with a complete randomized design trial (CRD) consisting of 3 treatments and 4 repeats including fucoidan supplementation at a dose of 0 mg/kg (control); 750 mg/kg; and 1500 mg/kg of feed. Every day, shrimp were fed as much as 3% of biomass with a frequency of 4 times. Four nonspecific immune response of shrimp including total hemocyte count (THC), phagocytosis activity (PA), phagocytosis index (PI), and total plasma protein (TPP) were mesured on day 0; 7; and 14 after fucoidan supplementation. The results showed the administration of fucoidan extract Padina sp. gives significantly different results to THC and TPP enhancements. Supplementation treatment of 750 mg/kg fucoidan Padina is the best treatment to increase nonspecific immune response in Pacific white shrimp.